A COMPARATIVE STUDY OF MATHEMATICAL TERMINOLOGY IN UZBEK AND ENGLISH (Bulletin of Innovative Research, 2026)
Mathematical terminology represents one of the most systematized and universal lexical domains in world languages. Despite the universal nature of mathematics as a scientific discipline, mathematical terms demonstrate language-specific semantic, morphological, and cultural characteristics. This study provides a comparative analysis of mathematical terminology in Uzbek and English from linguosemantic and linguocultural perspectives. The research investigates the historical development of mathematical terms, their derivational mechanisms, semantic classifications, metaphorical foundations, and cultural conceptualization of numerical categories. The study employs comparative-typological analysis, componential analysis, cognitive-semantic interpretation, and elements of corpus-based observation. The findings reveal that while mathematical terminology in both languages shares international roots, particularly Greco-Latin sources, Uzbek terminology demonstrates stronger derivational productivity and semantic adaptation, whereas English terminology reflects greater international standardization. Additionally, the cultural conceptualization of numbers differs in figurative usage, particularly in proverbs, idioms, and folklore. The study contributes to terminology theory, contrastive linguistics, and translation studies.